2010
DOI: 10.1002/jcla.20356
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and antioxidant enzyme activities in cancerous bladder tissue and their relation with bacterial infection: a controlled clinical study

Abstract: It is well known that antioxidants and reactive oxygen species play an important role in carcinogenesis. In this study, we attempted to evaluate antioxidant enzyme activities and lipid peroxidation levels in cancerous bladder tissue and to determine their relationship with bacterial infection. Bacterial culture was made from all urine samples using Blood and Eosin Methylene Blue agars for checking the presence of bacterial infections. We measured thiobarbituric acid reactive substances (TBARs) and activities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
(38 reference statements)
1
24
0
Order By: Relevance
“…In some diseases, an increase in reactive oxygen species is not the primary cause of the illness; it develops secondarily to the primary disorder and is involved in pathogenesis 14 . There are some studies indicating that oxidative stres plays a role in the pathogenesis of viral hepatitis, sepsis, and bacterial infections [15][16][17][18][19] . Numerous studies demonstrated that in many infectious diseases, a variety of inflammatory cells are activated, which lead to production of reactive oxygen and nitrogen species to kill parasites.…”
Section: Discussionmentioning
confidence: 99%
“…In some diseases, an increase in reactive oxygen species is not the primary cause of the illness; it develops secondarily to the primary disorder and is involved in pathogenesis 14 . There are some studies indicating that oxidative stres plays a role in the pathogenesis of viral hepatitis, sepsis, and bacterial infections [15][16][17][18][19] . Numerous studies demonstrated that in many infectious diseases, a variety of inflammatory cells are activated, which lead to production of reactive oxygen and nitrogen species to kill parasites.…”
Section: Discussionmentioning
confidence: 99%
“…This aliquot was spectrophotometrically analyzed, as described by Bayraktar et al [18] . Briefly, xanthine-xanthine oxidase was used to generate a superoxide flux.…”
Section: Superoxide Dismutase Activitymentioning
confidence: 99%
“…CAT prevents the accumulation of H 2 O 2 by catalyzing the rapid decomposition of H 2 O 2 to O 2 and H 2 O and it is one of the most important antioxidant enzymes. Although there are several reports that CAT activity is suppressed in cancerous tissues [22][23][24][25] , some authors found unchanged or increased activity in some tumor tissues 26,27 . Durak et al 22 found decreased CAT activity in cancerous bladder tissues.…”
Section: Resultsmentioning
confidence: 99%